2014
DOI: 10.1007/s11547-014-0436-6
|View full text |Cite
|
Sign up to set email alerts
|

Parotid glands in whole-brain radiotherapy: 2D versus 3D technique for no sparing or sparing

Abstract: Planning whole-brain radiotherapy with only the 2D technique involves a risk of including parotid glands in the field and not covering the clinical target volume. The 3D technique should be systematically performed and the parotid glands should be regarded as an organ at risk in whole-brain radiotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…In-depth clinical rational, feasibility studies for hippocampal-sparing WBRT including concurrent boost to brain metastatic diseases using modern radiotherapy systems, controversies, and future directions for hippocampal avoidance in cranial irradiation have also been discussed in a review article published by Kazda and colleagues. (29) Radiation-induced toxicity for WBRT patients has also been reported for other OARs such as parotid glands, (30,31) scalp, (32) and ear canals. (33) Radiation-induced toxicity to parotid glands is associated with xerostomia or dry mouth, impaired swallowing, and malnutrition, and unwanted scalp dose with hair loss.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In-depth clinical rational, feasibility studies for hippocampal-sparing WBRT including concurrent boost to brain metastatic diseases using modern radiotherapy systems, controversies, and future directions for hippocampal avoidance in cranial irradiation have also been discussed in a review article published by Kazda and colleagues. (29) Radiation-induced toxicity for WBRT patients has also been reported for other OARs such as parotid glands, (30,31) scalp, (32) and ear canals. (33) Radiation-induced toxicity to parotid glands is associated with xerostomia or dry mouth, impaired swallowing, and malnutrition, and unwanted scalp dose with hair loss.…”
Section: Discussionmentioning
confidence: 92%
“…Radiation‐induced toxicity for WBRT patients has also been reported for other OARs such as parotid glands, 30 , 31 scalp, (32) and ear canals (33) . Radiation‐induced toxicity to parotid glands is associated with xerostomia or dry mouth, impaired swallowing, and malnutrition, and unwanted scalp dose with hair loss.…”
Section: Discussionmentioning
confidence: 94%
“…It includes the brain tissue, skull, and spinal cord to the lower level of the atlas. However, Trignani et al [16] compared 2D-RT with 3D-CRT for WBRT and discovered that 28% of patients received a mean dose of >20 Gy in the parotid gland. Meanwhile, Noh et al [9] reported that mean parotid doses of ≥20 and ≥25…”
Section: Discussionmentioning
confidence: 99%
“…However, after the transition to the 3D era, by virtue of CT-simulation, it was possible to identify normal tissue dose distributions. Trignani et al compared the 2D technique with the 3D technique for WBRT, and discovered that 28% of patients received a mean dose in excess of 20 Gy to the parotid gland when using 2D-RT [12]. Noh et al also reported that the treatment fields encompassing the brain tissue, and the skull.…”
Section: Discussionmentioning
confidence: 99%
“…To avoid severe xerostomia, the Quantitative Analyses of Normal Tissue Effects in the Clinic (QUANTEC) guidelines recommend that the mean dose to at least one parotid gland should be less than 20 Gy or that the mean dose to the combined volume of both glands should be less than 25 Gy [11]. However Trignani et al showed that 28% of patients treated with conventional treatment received parotid gland doses beyond the recommended limits [12]. Noh et al have recently showed through the normal tissue complication probability model that the parotid gland should be considered an organ-at-risk (OAR) during WBRT [13].…”
Section: Introductionmentioning
confidence: 99%